The Impact of Atmospherics on Customer Experience at the Seattle Coffee Shop at Medstone Umhlanga - Vadivalu, Craig (The IIE, 2020)
This research investigated the impact that ambient factors such as lighting, sound, odours and design layout have on customers’ in-store experiences. Identifying the atmospheric variables and their impact on customer experience was beneficial as it will enable Seattle to enhance customer experience and improve the brand’s image. The problem was a perceived failure by Seattle, to identify positive and negative atmospheric contributors. This research followed a qualitative approach; it used mailed interview schedules and video-based interviews to elicit in-depth client information from 11 individuals who have visited or purchased from the café. This was appropriate as an in-depth description of client experiences was required. Furthermore, it prevented physical interaction during the COVID-19 pandemic. Findings indicated both the positive and negative atmospheric variables within Seattle. However, Seattle’s overall store atmosphere resulted in a positive customer experience, thus, resulting in a favourable perception of the brand. In addition, recommendations have been made as to how the brand cam improve the atmospherics in order to retain existing clients and attract new ones.
Keywords: Customer experience; Brand image; Atmospherics; Atmospheric stimuli; Interior design